Fire Control Efforts in a Cement Company in East Java - Trie Islamy Pangestu Astid Putera; Tri Meidya Rahmawati (Universitas Airlangga, 2021)
Introduction: The cement production process uses high technology machines and uses coal as fuel. The potential for fires is huge because in the cement company there are areas that are very vulnerable to fires such as in the coalmill, preheater, and klin areas. The purpose of this study is to describe the description of the causes of fires, fire prevention technical efforts, OSH organization in the field of fire prevention, and personal protective equipment (PPE). Methods: The method used in this research was a descriptive method with cross sectional study design. Data collection was done by means of observation. The research variables used were the causes of fire, fire prevention technical efforts, OSH organization in the field of fire prevention, and Personal Protective Equipment (PPE) for firefighters. The sample used in this study was the entire unit in the cement company. Result: Cement company causes fires, classified in medium criteria. Meanwhile, fire prevention efforts in the cement company is classified in good criteria. Moreover, organizations in the cement company in the fire prevention sector is included in good criteria and the personal protective equipment provided in the cement company is included in good criteria. Conclusion: The cause of the fire in the cement company is the use of coal as the main fuel for the process of making cement, which is also the source of fire. Efforts made by the cement company include the installation of layouts and the installation of evacuation signs on each building. Personal Protective Equipment in the cement company has also been well managed.Keywords: cement, coal, fire, occupational safety and health, personal protective equipment